Auditing an urban park deck with 3D geovisualization—A comparison of in-situ and VR walk-along interviews - Jaalama Kaisa; Rantanen Toni; Julin Arttu; Fagerholm Nora; Keitaanniemi Aino; Virtanen Juho-Pekka; Handolin Hannu; Vaaja Matti; Hyyppä Hannu (ELSEVIER GMBH, 2022)
Virtual reality-based urban audit methods are gaining increasing attention; however, most virtual urban audit studies have focused on panoramic views. The 3D city model-based geovisualizations have remained until now rather unexplored in user studies for urban audits and for communicative urban planning. We explored the feasibility of a 3D geovisualization-based urban audit in virtual reality (VR) for assessing the perceived quality of an urban park deck in Helsinki, Finland. For this purpose, we created a photorealistic and geometrically accurate 3D model (Bryga 3D) based on photogrammetric and laser scanning data. Bryga 3D was implemented on a game engine to be viewed with a head-mounted VR display. Bryga 3D's ability to convey information in a subjective urban audit, that is, subjectively perceived affordances of a park deck, was tested in a walk-along interview study comparing auditing in situ and via the VR method. A comparison of the results with in-situ (n = 13) and VR interviews (n = 21) show that the perception of several tangible elements, such as spatial division, landforms, paths, and chairs when using Bryga VR was similar to when performed in situ. Perception of vegetation was weaker in VR in terms of its detailed quality, which somewhat affected the presented development ideas and assessment of the seasonal context. Also, weaker perception of the surroundings and city context affected the results in VR. However, considering that Bryga 3D presents an example of a highly automated 3D city modeling process conducted with minimal manual work, its results are encouraging for future attempts to advance such realizations for the purposes of communicative urban planning. 3D geovisualization-based virtual audits could be used when urban green space audits are not possible or when they are demanding to implement in situ.